Avaliação dos níveis de proteína C-reativa ultra-sensível em pacientes com periodontite crônica severa generalizada e sem periodontite - Bezerra, Candice de Freitas Rêgo (2007)
INTRODUCTION: The high sensitivity C-reactive protein (hsCRP) constitutes an inflammatory mediator used as predictor of cardiovascular risk that comes being researched as indicative relation factor between cardiovascular and periodontal diseases. PROPOSITION: To compare serumals levels of C-reactive protein between patients with and without generalized severe chronic periodontitis. METHODOLOGY: A seccional study was realized using a sample with 62 patients, being 31 participants carriers of periodontal diseases (Group I) and 31 without periodontal diseases (Group II), grouped to the pairs by age and sex. As inclusion criterio were selected patients with diagnosis of generalized severe chronic periodontitis, being preculeds, individuals which presented systemic disease, recent infection history, historical of CVA or stroke, smokers, pregnants and lactants. The research consisted of two stages, a clinc and other biochemist. The clinical stage is constituted of periodontal examination and the biochemist stage, of the peripheral blood collection for determination hsCRP levels and a hemogram to inquire any panel which could suggest infectious and/or inflammatory process. RESULTS: Periodontal disease group presented a average of 0,36mg/dL, while the group without disease presented 0,17 mg/dL, do not existing significant difference statistically between the averages (p = 0,061). The cardiovascular risk for the group I was classified high for 27,6% of participants and low for 72,4% of them. In the group II, 6,45% presented high risk e 93,5% low risk, being this significant relation statistically gotten for Fisher s Test (p = 0,042) presenting OR = 5,33; IC = 95% (1,02 27,4). The independets variables reseacred do not presented significant association statistically with the levels of hsCRP. CONCLUSION: The study indicated that despite of carriers patients of periodontal diseases do not present differents serumals levels of hsCRP from the other group, the periodontal disease was considered as risk factor for hsCRP plasmatic levels elevation